Injury consequences from participation in professional rugby league: a preliminary investigation. Issue 2 (June 1997) - Meir, R A; McDonald, K N; Russell, R
Abstract : OBJECTIVE: To conduct a preliminary investigation to determine if injuries sustained while playing professional rugby league have long term consequences for players after retirement from their playing careers. METHOD: Twenty eight retired players, who had competed in the professional Australian Rugby League competition, responded to a 23 item survey. Respondents were asked to recall all injuries that resulted in them being unable to play for five or more consecutive games. The survey asked players to provide information about age, playing weight, number of games played, position played, number and type of major injuries sustained during their career, and the effects of these injuries both during their career and after retirement. RESULTS: Within the limitations of this study's small sample, it is suggested that players with long term consequences of injury may experience a variety of detrimental effects into retirement, including job limitations, reduced income earning potential, and increased personal medical costs. CONCLUSION: Although research relating to the type and severity of injuries sustained while playing rugby league has been previously undertaken, investigation into the effect injuries sustained during a professional career have on players after retirement has been neglected. This preliminary investigation suggests that retired professional rugby league players may have at least one long term consequence of injuries sustained during their playing career.